Status Kewarganegaraan Anak Yang Terlahir Dari Ibu WNI Dan Ayah WNA Setelah Berlakunya Undang-Undang Nomor 12 Tahun 2006 Tentang Kewarganegaraan Republik Indonesia - tika andarasni parwitasari (Jurnal Ilmiah SINUS, 2010)
Citizenship Status of Children is an important thing for life and the future of the children later. For a child who is born of father and mother who has the same nationality, of course, will not cause significant problems. However, if the child born of a mother Indonesian citizen and a foreign citizen father, certainly it would potentially cause problems. The general overwiew section of Citizenship Law of the Republic of Indonesia explained that the meaning of citizenship is any kind of relationship between people and countries that lead the country's obligation to protect the person concerned. In this case between the state and its citizens have a juridical relationship. A citizen is a full member of the country concerned and have certain rights and obligations towards his country. Instead the state is obliged to protect its citizens in whatever form and wherever they are. Citizenship Status of Children born to an Indonesian citizen mother and a father foreigners before the enactment of Law No. 12 of 2006 then his citizenship necessarily follow the citizenship status of his father, but after the enactment of this Law the children has two citizenship, both from his fathers nationality and his mothers nationality. Dual citizenship granted to children is a limited dual citizenship for children, where the child after the age of 18 years or has been married must declare to choose one citizenship.Keywords : citizenship, children